Exploring the complex pre-adaptations of invasive plants to anthropogenic disturbance: a call for integration of archaeobotanical approaches - Bellini, Ginevra; Schrieber, Karin; Kirleis, Wiebke; Erfmeier, Alexandra (Frontiers in Plant Science, 2024)
Pre-adaptation to anthropogenic disturbance is broadly considered key for plant invasion success. Nevertheless, empirical evidence remains scarce and fragmentary, given the multifaceted nature of anthropogenic disturbance itself and the complexity of other evolutionary forces shaping the (epi)genomes of recent native and invasive plant populations. Here, we review and critically revisit the existing theory and empirical evidence in the field of evolutionary ecology and highlight novel integrative research avenues that work at the interface with archaeology to solve open questions. The approaches suggested so far focus on contemporary plant populations, although their genomes have rapidly changed since their initial introduction in response to numerous selective and stochastic forces. We elaborate that a role of pre-adaptation to anthropogenic disturbance in plant invasion success should thus additionally be validated based on the analyses of archaeobotanical remains. Such materials, in the light of detailed knowledge on past human societies could highlight fine-scale differences in the type and timing of past disturbances. We propose a combination of archaeobotanical, ancient DNA and morphometric analyses of plant macro-and microremains in order to assess past community composition, and species' functional traits in order to unravel the timing of adaptation processes, their drivers and their long-term consequences for invasive species. Although such methodologies have proven to be feasible for numerous crop plants, they have not been yet applied to wild invasive species, which opens a wide array of insights into their evolution.